Gambaran Tingkat Pengetahuan Ibu Postpartum Primipara Tentang Perubahan Fisiologis Pada Masa Nifas Di BPM Hj. Syarifah Noor Hasanah,S.ST Loktabat Utara Banjarbaru Tahun 2016 - Ni Wayan Kurnia Widya Wati; Putri Ratnasari (Jurnal Kesehatan Indonesia, 2017)
At childbed phase, there are some physiologically changes on mother’s body system. Those changes occur on reproduction system, digestion system, urine system, musculoskeletal, changes of vital such as cardiovascular and hematologic.This research is aimed to observe postpartum primipara mothers’ knowledge level about physiologically changes at childbed phase in BPM (midwife’s practice officially office) Hj. Syarifah Noor Hasanah, S. ST., North Loktabat, Banjarbaru, 2016. This research uses descriptive research method. Sampling technique uses Total Sampling such as 45 respondents. Most of them have enough knowledge as 18 people (40,0%), then, 15 people of them have low knowledge (33,3%), while the rest have good knowledge as 12 people (26,7%).Based on this research, advised to midwives who practice officially to increase primipara mothers’ knowledge through counseling activity about physiologically changes at childbed phase, and advised to primipara mothers to check themselves up regularly at least 4 times at that phase, so risk factors can early detected, reported, and they will be sent to better medical institution, they can look information about physiologically changes at childbed phase through book, newspaper and also counseling activity phase